Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure, let's work through the problem step-by-step.
Given:
[tex]\[ M = \begin{pmatrix} 2 & -1 \\ 4 & 6 \end{pmatrix} \][/tex]
[tex]\[ N = \begin{pmatrix} -3 & 0 \\ 4 & 1 \end{pmatrix} \][/tex]
### Step 1: Calculate the transposes of [tex]\( M \)[/tex] and [tex]\( N \)[/tex]
1. Transpose of [tex]\( M \)[/tex]
[tex]\[ M' = \begin{pmatrix} 2 & 4 \\ -1 & 6 \end{pmatrix} \][/tex]
2. Transpose of [tex]\( N \)[/tex]
[tex]\[ N' = \begin{pmatrix} -3 & 4 \\ 0 & 1 \end{pmatrix} \][/tex]
### Step 2: Calculate the sum of the transposes [tex]\( M' + N' \)[/tex]
[tex]\[ M' + N' = \begin{pmatrix} 2 & 4 \\ -1 & 6 \end{pmatrix} + \begin{pmatrix} -3 & 4 \\ 0 & 1 \end{pmatrix} = \begin{pmatrix} 2 + (-3) & 4 + 4 \\ -1 + 0 & 6 + 1 \end{pmatrix} = \begin{pmatrix} -1 & 8 \\ -1 & 7 \end{pmatrix} \][/tex]
### Step 3: Calculate [tex]\( M + N \)[/tex]
[tex]\[ M + N = \begin{pmatrix} 2 & -1 \\ 4 & 6 \end{pmatrix} + \begin{pmatrix} -3 & 0 \\ 4 & 1 \end{pmatrix} = \begin{pmatrix} 2 + (-3) & -1 + 0 \\ 4 + 4 & 6 + 1 \end{pmatrix} = \begin{pmatrix} -1 & -1 \\ 8 & 7 \end{pmatrix} \][/tex]
### Step 4: Calculate the transpose of [tex]\( M + N \)[/tex]
[tex]\[ (M + N)' = \left( \begin{pmatrix} -1 & -1 \\ 8 & 7 \end{pmatrix} \right)' = \begin{pmatrix} -1 & 8 \\ -1 & 7 \end{pmatrix} \][/tex]
### Step 5: Compare [tex]\( M' + N' \)[/tex] with [tex]\( (M + N)' \)[/tex]
We have:
[tex]\[ M' + N' = \begin{pmatrix} -1 & 8 \\ -1 & 7 \end{pmatrix} \][/tex]
[tex]\[ (M + N)' = \begin{pmatrix} -1 & 8 \\ -1 & 7 \end{pmatrix} \][/tex]
Since [tex]\( M' + N' = (M + N)' \)[/tex], they are equal.
Given:
[tex]\[ M = \begin{pmatrix} 2 & -1 \\ 4 & 6 \end{pmatrix} \][/tex]
[tex]\[ N = \begin{pmatrix} -3 & 0 \\ 4 & 1 \end{pmatrix} \][/tex]
### Step 1: Calculate the transposes of [tex]\( M \)[/tex] and [tex]\( N \)[/tex]
1. Transpose of [tex]\( M \)[/tex]
[tex]\[ M' = \begin{pmatrix} 2 & 4 \\ -1 & 6 \end{pmatrix} \][/tex]
2. Transpose of [tex]\( N \)[/tex]
[tex]\[ N' = \begin{pmatrix} -3 & 4 \\ 0 & 1 \end{pmatrix} \][/tex]
### Step 2: Calculate the sum of the transposes [tex]\( M' + N' \)[/tex]
[tex]\[ M' + N' = \begin{pmatrix} 2 & 4 \\ -1 & 6 \end{pmatrix} + \begin{pmatrix} -3 & 4 \\ 0 & 1 \end{pmatrix} = \begin{pmatrix} 2 + (-3) & 4 + 4 \\ -1 + 0 & 6 + 1 \end{pmatrix} = \begin{pmatrix} -1 & 8 \\ -1 & 7 \end{pmatrix} \][/tex]
### Step 3: Calculate [tex]\( M + N \)[/tex]
[tex]\[ M + N = \begin{pmatrix} 2 & -1 \\ 4 & 6 \end{pmatrix} + \begin{pmatrix} -3 & 0 \\ 4 & 1 \end{pmatrix} = \begin{pmatrix} 2 + (-3) & -1 + 0 \\ 4 + 4 & 6 + 1 \end{pmatrix} = \begin{pmatrix} -1 & -1 \\ 8 & 7 \end{pmatrix} \][/tex]
### Step 4: Calculate the transpose of [tex]\( M + N \)[/tex]
[tex]\[ (M + N)' = \left( \begin{pmatrix} -1 & -1 \\ 8 & 7 \end{pmatrix} \right)' = \begin{pmatrix} -1 & 8 \\ -1 & 7 \end{pmatrix} \][/tex]
### Step 5: Compare [tex]\( M' + N' \)[/tex] with [tex]\( (M + N)' \)[/tex]
We have:
[tex]\[ M' + N' = \begin{pmatrix} -1 & 8 \\ -1 & 7 \end{pmatrix} \][/tex]
[tex]\[ (M + N)' = \begin{pmatrix} -1 & 8 \\ -1 & 7 \end{pmatrix} \][/tex]
Since [tex]\( M' + N' = (M + N)' \)[/tex], they are equal.
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.